2017
DOI: 10.1016/j.marenvres.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage in dab (Limanda limanda) and haddock (Melanogrammus aeglefinus) from European seas

Abstract: Dab (Limanda limanda) and haddock (Melanogrammus aeglefinus) were collected from coastal and offshore locations in the Baltic (dab only), North Sea (haddock from one location only) and Iceland. Blood was analysed for DNA strand breaks using the comet assay and liver samples for DNA adduct concentrations. DNA strand breaks were at background levels in dab from the two Iceland locations and from the Dogger Bank. The highest levels were observed in dab from the Firth of Forth, Ekofisk and the German Bight. Hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The method was adopted for more than 90 different species [53] and as it requires relatively small cell samples, it could be suitable for all 30.000 different fish species, at least theoretically. Until now the method was developed for fish of only a few centimetres in size [77] up to more than two meters [78], including fish that live in various environments; from arctic [79] to tropical waters [80], seas [81] to fresh waters [82], bottom feeder fish [83] and open water fish [84]. Nevertheless, one group of fish, namely cartilaginous fish that include sharks, rays, skates, sawfish and chimaeras, are still completely overlooked and to the best of our knowledge, there are no studies describing the comet assay in Chondrichthyes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…The method was adopted for more than 90 different species [53] and as it requires relatively small cell samples, it could be suitable for all 30.000 different fish species, at least theoretically. Until now the method was developed for fish of only a few centimetres in size [77] up to more than two meters [78], including fish that live in various environments; from arctic [79] to tropical waters [80], seas [81] to fresh waters [82], bottom feeder fish [83] and open water fish [84]. Nevertheless, one group of fish, namely cartilaginous fish that include sharks, rays, skates, sawfish and chimaeras, are still completely overlooked and to the best of our knowledge, there are no studies describing the comet assay in Chondrichthyes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Nevertheless, the multi-tissue approach in aquatic biomonitoring studies is rare but highly recommended. Recently Hylland et al [81] showed that the samples already embedded in agarose on gelbond films can be stored in lysis for several weeks which is a benefit in field studies. Additionally, the comet assay was modified also for whole fish embryos, usually zebrafish (Danio rerio) [88][89][90].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Mediterranean population, bulky DNA adducts are correlated with environment ozone pollution that contributes to photochemical smog [ 34 ]. Hylland et al [ 35 ] used DNA adducts as signature biomarker to examine the extent of pollution at various locations in the Northeast Atlantic region near to coastal and offshore. Adduct as a biomarker (DNA adduct) alerts risk exposure by providing early warning information and assisting in improving hazard assessment for aquatic organisms and ecological risk assessment [ 36 ].…”
Section: Application Of Adductomicsmentioning
confidence: 99%